2020
DOI: 10.1093/mnras/staa158
|View full text |Cite
|
Sign up to set email alerts
|

A survey for variable young stars with small telescopes: II – mapping a protoplanetary disc with stable structures at 0.15 au

Abstract: The HOYS citizen science project conducts long-term, multifilter, high-cadence monitoring of large YSO samples with a wide variety of professional and amateur telescopes. We present the analysis of the light curve of V1490 Cyg in the Pelican Nebula. We show that colour terms in the diverse photometric data can be calibrated out to achieve a median photometric accuracy of 0.02 mag in broad-band filters, allowing detailed investigations into a variety of variability amplitudes over time-scales from hours to seve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Afterwards the colour correction is applied to all stars. In Evitts et al (2020) we have shown that this results in typical photometric uncertainties of the broad band photometry of a few percent. In Fig.…”
Section: Hoys Datamentioning
confidence: 77%
See 4 more Smart Citations
“…Afterwards the colour correction is applied to all stars. In Evitts et al (2020) we have shown that this results in typical photometric uncertainties of the broad band photometry of a few percent. In Fig.…”
Section: Hoys Datamentioning
confidence: 77%
“…The star is found near (slightly south) of the sub-cluster 5 identified in the Spitzer/IRAC survey by Guieu et al (2009), but is not listed in their catalogue of YSOs (presumably due to lack of infrared excess, see below). The Gaia DR2 parallax of 2.44 ± 0.02 mas (Gaia Collaboration 2018), places the star at a distance of 405 ± 3 pc (Bailer-Jones et al 2018), whereas IC 5070 has a significantly larger distance, recently estimated as 870 +70 −55 pc (Evitts et al 2020). Thus, V1598 Cyg is a foreground star and does not belong to the star forming region.…”
Section: V1598 Cyg In the Literaturementioning
confidence: 98%
See 3 more Smart Citations